The Impact Innovation Policy and Industrial Competitiveness - Valentinavičius, Stasys (Ekonomika, 1999)
The impact of innovations on economic growth, restructuring and industrial competitiveness has been analysed in the article. The types of innovation policies, their formation and practical experience in industrial countries are being reviewed. The problems of using of innovation potential and problems of competitiveness enlargement are analysed. Concrete proposals on innovation policy and financial funds in Lithuania are given.